PENINGKATAN KAPASITAS SDM UMKM PURBALINGGA MELALUI PENGUATAN KOMPETENSI DAN DIGITALISASI BERBASIS KEARIFAN LOKAL - Barima, Hima (ABDI MAKARTI, 2025)
This community service activity was conducted in Babakan Village, Kalimanah District, Purbalingga Regency to improve the human resource capacity of Micro, Small, and Medium Enterprises (MSMEs). The main challenges identified were limited knowledge of human resource management, low digital literacy, and minimal application of local values in business practices. The program included observation, training, mentoring, practice sessions, evaluation, and the establishment of an MSME community. The results show that participants gained better understanding of human resource management, improved digital marketing skills, and greater awareness of applying local values in their businesses. Several MSME actors successfully created online store accounts and used social media for promotion. In addition, an MSME community was formed as a platform for collaboration and sustainability. This program demonstrates that strengthening human resources through training, mentoring, and cultural integration can enhance the independence, professionalism, and competitiveness of village MSMEs. Further support and follow-up activities are needed to ensure continuity and long-term impact.